2008
DOI: 10.5802/jedp.31
|View full text |Cite
|
Sign up to set email alerts
|

High frequency limit of Helmholtz equations: the case of a discontinuous index

Abstract: In this text, we compute the high frequency limit of the Hemholtz equation with source term, in the case of a refraction index that is discontinuous along a sharp interface between two unbounded media. The asymptotic propagation of energy is studied using Wigner measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…We were able to observe a transient spectrum around 780 nm with a lifetime of approximately 50 μs for 1 in ethanol, but not in glycerol, that matches the spectrum reported previously for the photoisomer of the same dye in DMSO. 19 No transient signals were observed for 2 in either solvent, providing strong evidence that photoisomerization was blocked due to installation of the ring system. We also carried out fluorescence correlation spectroscopy (FCS) measurements, which have been previously used to characterize photoisomerization in Cy5 and other unrestricted cyanines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to observe a transient spectrum around 780 nm with a lifetime of approximately 50 μs for 1 in ethanol, but not in glycerol, that matches the spectrum reported previously for the photoisomer of the same dye in DMSO. 19 No transient signals were observed for 2 in either solvent, providing strong evidence that photoisomerization was blocked due to installation of the ring system. We also carried out fluorescence correlation spectroscopy (FCS) measurements, which have been previously used to characterize photoisomerization in Cy5 and other unrestricted cyanines.…”
Section: Resultsmentioning
confidence: 99%
“…13 Also consistent with a role for photoisomerization, albeit nonquantitatively, transient spectroscopy studies directly observed the isomerized species, as does as an approach using gas-phase mass spectrometry. 14,15 By contrast, a study looking at two highly substituted heptamethine cyanines found that room-temperature emission was independent of solvent viscosity. 16 This observation suggests that, at least in these examples, the contribution of photoisomerization to nonradiative singlet-state deactivation is insignificant.…”
Section: Introductionmentioning
confidence: 97%